Template-assisted covalent modification underlies activity of covalent molecular glues - Li, Yen-Der; Ma, Michelle W.; Hassan, Muhammad Murtaza; Hunkeler, Moritz; Teng, Mingxing; Puvar, Kedar; Rutter, Justine C.; Lumpkin, Ryan J.; Sandoval, Brittany; Jin, Cyrus Y.; Schmoker, Anna M.; Ficarro, Scott B.; et al. (Nature chemical biology, 2024)
Molecular glues are proximity-inducing small molecules that have emerged as an attractive therapeutic approach. However, developing molecular glues remains challenging, requiring innovative mechanistic strategies to stabilize neoprotein interfaces and expedite discovery. Here we unveil a trans -labeling covalent molecular glue mechanism, termed ‘template-assisted covalent modification’. We identified a new series of BRD4 molecular glue degraders that recruit CUL4 DCAF16 ligase to the second bromodomain of BRD4 (BRD4 BD2 ). Through comprehensive biochemical, structural and mutagenesis analyses, we elucidated how pre-existing structural complementarity between DCAF16 and BRD4 BD2 serves as a template to optimally orient the degrader for covalent modification of DCAF16 Cys58 . This process stabilizes the formation of BRD4–degrader–DCAF16 ternary complex and facilitates BRD4 degradation. Supporting generalizability, we found that a subset of degraders also induces GAK–BRD4 BD2 interaction through trans -labeling of GAK. Together, our work establishes ‘template-assisted covalent modification’ as a mechanism for covalent molecular glues, which opens a new path to proximity-driven pharmacology. Characterization of DCAF16-based BRD4 molecular glue degraders revealed a trans -labeling mechanism termed ‘template-assisted covalent modification’, which opens a new path for proximity-driven pharmacology.